Perlindungan Hukum Terhadap Pekerja Migran Indonesia - Fernando Hamonangan (CV Rewang Rencang, 2025)
The state should provide guarantees for rights and opportunities, as well as provide protection for every citizen without discrimination to obtain decent work and income according to their abilities and skills, both domestically and abroad. So far, the government still seems less serious in handling the protection of migrant workers, resulting in cases of violence, arbitrariness, human trafficking, and other treatments that violate human rights. This legal research is a doctrinal legal research that discusses the implementation of protection for Indonesian Migrant Workers before, during, and after working abroad and the protection provided by Law Number 18 of 2017 concerning Protection of Indonesian Migrant Workers which replaces Law Number 39 of 2004 concerning Placement and Protection of Indonesian Migrant Workers Abroad. Protection of Indonesian Migrant Workers can be implemented optimally as long as the relevant parties can seriously implement the provisions in existing laws and regulations.